Analisis Kritis Terhadap Metodologi Pengajaran Tarannum Al-Quran di Malaysia - Nurul Saadah Mohammad Zaini; Anuar Hasin; Robiatul Adawiyah Mohd @ Amat (Penerbit USIM, 2025)
International Conference of Quran as Foundation of Civilization (SWAT 2025) : Maqasid al-Quran and the Madani Vision: A Guiding Light for Regional Serenity and Global Unity Organized by : Faculty of Quranic and Sunnah Studies, in collaboration with Nasyrul Quran and Daffodil International University, Bangladesh. Date:12-13 November 2025